Penerapan Model Pembelajaran SAVI dan LT Terhadap Prestasi Belajar Siswa Kelas VIII di MTs - Siti Rokhmah Rokhmah; Prasetyo Budi Darmono; Heru Kurniawan (Universitas Muhammadiyah Purworejo, 2022)
This study aims to determine that the mathematics learning achievement of students who use the SAVI learning model is better than that of students who use the LT learning model in class VIII students in MTs. This study used 2 classes, namely class VIII A and VIII C, which were obtained using simple random sampling. Methods of data collection using the method of documentation and tests. The normality test uses the Lilliefors method, the homogeneity test of variance uses the Bartlett method, the balance test uses the t-test, and the hypothesis test uses the t-test with a significant level of = 0.025. The average control class was 77,226, and the experimental class was 79,194. The results of hypothesis testing using the right-hand t-test obtained count = 0.492 while table = 2.299, DK = t|t > 2.299, this indicates that count DK. The conclusion of this study is that H0 is accepted, meaning that the mathematics learning achievement of students using the Somatic, Auditory, Visual, Intellectual (SAVI) learning model is not better than the mathematics learning achievement of students using the Listening Team learning model in class VIII students in MTs. The formation of groups from the two cooperative learning models, namely Somatic, Auditory, Visual, Intellectual (SAVI) and Listening Teams, resulted in both models giving the same results when applied in the classroom. Therefore, both models can contribute to improving student achievement.